ISSUES RELATING TO LENDING ACTIVITY IN ALBANIAN BANKING SECTOR - Petanaj, Migena; Durmishi, Veronika (European Scientific Journal, ESJ, 2015)
The banking sector in Albania is among the most developed sectors of the Albanian economy and one of the few, whose development can be compared to that of other countries of the world. With the recent financial crisis of 2008 the world economy suffered a heavy blow, especially with regard to the global financial systems. Albania, although with no immediate consequences of this crisis by being less exposed to the international financial markets, has started to show problems in its development rates. One of the main problems of the Albanian economy, especially in recent years, is the high rate of non-performing loans in the Albanian economy. Following 2008 this indicator has seen a large increase making today Albania a country with the highest non-performing loans rate in region. The article is aimed at providing a detailed analysis on the problems encountered in Albania regarding private borrowing as well as at making a comparison with other countries in the region. This goal will be achieved by analyzing the banks' lending activity through a questionnaire addressed to the second-tier banks operating in Albania. This questionnaire shall help to make an assessment of monetary and economic development of the country, following the collection of certain data on some key issues of the lending process, such as loan approval standards, terms of lending to businesses and individuals, trends in demand for loans, etc